Experimental Investigation on Velocity Fields of Seepage Flow Inside Gravel Mount (Journal of Environmental Science Studies, 2023)
There is little information on velocity field of seepage flows. The formation of seepage flow is significant for aquatic habitat including spawning of aquatic animals in river. To create spawning fields in river, the stability of a heaped-up gravels during floods is required for its artificial formation. The velocity measurement of seepage flows is also necessary. This paper presents velocity fields of seepage flows in a heaped-up gravels. The experimental study yields that the heaped-up gravels are stabilized by installing the consecutively assembled boulders on the gravels. Also, small mean velocity and standard deviation are recorded for different discharges. Spectrum analysis reveals that fluctuation velocity of seepage flows depends on the turbulent flow above the heaped-up gravels.